Management of stent-related tracheoesophageal fistula in complex post-tuberculosis tracheobronchial stenosis: A case report - Bai, Yang; Yin, Yuting; Chi, Jing; Li, Shuang; Li, Yishi; Guo, Shuliang (Frontiers in Medicine, 2022)
Background: The covered self-expandable metallic stents (SEMS) have been used to manage benign tracheobronchial stenosis, especially the complex post-tuberculosis (TB) tracheobronchial stenosis (PTTS) with cartilage destruction or malacia. This procedure could lead to stent-related tracheoesophageal fistula (TEF). Case presentation: A 21-year-old woman, who had one covered Y-shaped SEMS inserted to manage complex PTTS two years ago, presented with dyspnea and frequent coughing on drinking water. The bronchoscopy confirmed extensive granulation tissue hyperplasia and a TEF on the upper edge of the covered SEMS. The covered SEMS was removed in three steps, and another fully covered Y-shape SEMS (Microtech Co, Ltd, Nanjing, China) was inserted to restore patency in the tracheobronchial tree and occlude the TEF orifice. Recombinant bovine basic fibroblast growth factor (rbFGF) (6000IU/time) was sprayed into and around the fistula through the V-System single-use cannula via the flexible bronchoscope every other week. The patient showed sustained clinical and radiographic improvement, and the TEF healed. Conclusions: We presented a three-step bronchoscopic approach to managing a stent-related TEF in a patient with complex PTTS. Subsequently, regular bronchoscopic debridement of granulation tissue developing on the upper edge of SEMS is necessary to maintain the stent patency and reduce the risk of recurrent stent-related TEF. A fully covered SEMS associated with the local administration of rbFGF seems to offer an alternative simplified one-stage procedure for the temporary management of TEF combined with complex PTTS in non-surgical candidates.